Is Gold the Glittering Future Asset or just an over-valued Commodity? - Kumar, Ashish (International Journal of Psychosocial Rehabilitation, 2020)
In this paper all the aspects and versions of “gold” shall be discussed and analysed in deep to find out the reason for its ever increase in price over and over again. Is Gold really the worth of its value and can be said as a safe investment which can be stored for future purpose or is gold just an over rated and over-valued commodity due to the market sentiments and follow the herd instinct. There are few comparisons also made with all the major sought after investment deals i.e. gold, Silver and the stock market by which any investor can get his desired return in the time frame. So after analyzing all details we shall be able to conclude weather Gold is really a good future option from the perspective of investment or its just has been over valued over a period time following the herd instinct. Should an investor really put his hard-earned money in this little commodity which still seems priced too high for a common man.